PENGARUH PENGGUNAAN ICE BREAKING DALAM PELAJARAN IPAS TERHADAP MOTIVASI BELAJAR SISWA KELAS IV MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Dhea Mutia Jameliani; Dede Indra Setiabudi; Iis Humaeroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using ice breaking activities on students’ learning motivation in Natural and Social Sciences (IPAS) subjects for fourth-grade students at MI Ma’had Al-Zaytun. The research method used is a quantitative approach with a Pre-Experimental Design, employing a one-group pretest-posttest design. Data were collected through tests and questionnaires, with 44 fourth-grade students at MI Ma’had Al-Zaytun selected using purposive sampling techniques. Data analysis was carried out through normality tests, homogeneity tests, and Paired Sample T-Test using SPSS version 23. The results showed that the Paired Sample T-Test value was 0.000 (< 0.05), indicating that there is an effect of using ice breaking activities on students’ learning motivation. The average score increased from 65.16 in the pretest to 75.59 in the posttest, with a mean difference of 10.43 points. In addition, the questionnaire results showed that 66.71% of respondents gave positive and enthusiastic responses toward the use of ice breaking, indicating that this method is able to create a more enjoyable and interactive learning atmosphere. Based on these findings, it can be concluded that the use of ice breaking activities can be applied in IPAS learning for fourth-grade students at MI Ma’had Al-Zaytun, as it has a positive effect on students’ learning motivation. Keywords: Ice Breaking, Motivation, Natural and Social Sciences.